Medical students’ perception of supervision in MedUniVienna’s structured internal medicine and surgery clerkship program: Subject-specific differences and clerkship sequence effects - Hofhansl, Angelika; Zlabinger, Gerhard; Bach, Lena; Röhrs, Josefine; Mayer, Anna-Maria; Rieder, Anita; Wagner-Menghin, Michaela (GMS Journal for Medical Education)
Background: Clerkships for supervised learning of clinical skills are part of modern medical curricula. The availability of clerkship placements in clinics and the provision of competent supervision are essential for effective work-based learning. The scheduling of compulsory and elective work-based learning opportunities for undergraduate medical students (UGMS), especially when their numbers are high, results in varying clerkship sequences, which can influence career plans and examination outcomes. The effect of different clerkship sequences on students' impressions of clinical supervision remains unclear. Therefore, this study describes subject-specific differences in students' perceptions of clinical supervision during surgical (SC) and internal medicine (IMC) clerkships and addresses the impact of varying clerkship sequences and increasing clinical experience thereon. Method: In this survey, 1,017 final-year students at the Medical University of Vienna (from 2015 to 2019) retrospectively evaluated the quality of supervision they received during the SC and IMC using a newly piloted questionnaire on supervisory roles. Results: Students described their supervisors as less likely to exercise the roles of gatekeeper/safeguarding, training, and mentoring during the SC than during the IMC. During IMC, the supervisory activities received most often were to ensure patient and trainee safety, whereas during SC, it was to ensure trainee safety and to teach techniques and procedures. Ensuring an appropriate level of clinical duty was the third highest priority in both clerkships. Students’ general clinical experience influenced how they perceived the supervision, with students completing SC later in their pathway reporting having received similar levels of supervision in both clerkships. Conclusions: Supervision experiences during the first clerkship appear to shape students’ expectations of subsequent supervision. Providing additional support to foster a strong supervisory relationship, tailored to meet the specific supervision needs of UGMS newly entering year 6, could benefit both supervisors and students.